Implementation of Scientific Methods and Attitudes in Science Education - Septiliana, Lilla; Surul, Rofiatus (EDUCATIO : Journal of Education, 2023)
Primary school is the initial stage of formal education that provides students with fundamental knowledge and skills. Therefore, primary school education should emphasize meaningful learning experiences to help students develop their potential and abilities. One of the subjects taught at the primary school level is Natural Sciences (IPA - Ilmu Pengetahuan Alam). The teaching of Natural Sciences requires scientific methods and attitudes to ensure that students can develop a deep understanding of scientific concepts and apply them in their daily lives. The main focus of this article is on scientific methods and attitudes. Based on this research, the method used by the researcher is literature review. The research results show that the strategy for developing investigative skills and critical thinking in scientific methods and attitudes, using the Problem-Based Learning (PBL) model, is effective. This is because the learning model uses real-world problems as a context for students to learn problem-solving skills and critical thinking to acquire essential knowledge and concepts.